Estimates of Sexual Functioning in Married Men and Women - Arshad, Tehreem (Journal of Liaquat University of Medical & Health Sciences, 2019)
OBJECTIVE: To have estimation of sexual functioning in married men and women in Lahore, Pakistan. METHODOLOGY: This is a cross sectional design study, Community Sample was drawn from lower, middle and upper union councils of Data Ganj Bukhsh Town, Lahore to ensure representation of all socioeconomic statuses. Sample of 300 married participants including both genders who could read and understand Urdu language, with age range of 25 to 60 years were included after approval. All individuals who had some serious psychiatric or physical disorder which could have co-occurred with the sexual dysfunctions were excluded from the study. Data was analyzed by SPSS. Sexual Functioning Questionnaire was used to assess the overall sexual functioning of the participants. RESULTS: The results of the study suggested that participants had adequate sexual functioning (41% men, 32% women). In exploration of the problems faced by individuals in their sexual life, most of the participants had reported difficulties in experiencing interest (49% men, 48% women) and having sexual desire (55% men, 45% women) during the sexual activity. CONCLUSION: It is concluded that most of the participants had adequate overall sexual functioning but also have some sexual concerns like lack of interest and desire to take part in sexual activities.